Clinical and research developments in the treatment of paediatric obsessive-compulsive disorder - Watson, Hunna J (Curtin University, 2007)
It is of crucial importance to identify and disseminate effective treatments for paediatric obsessive-compulsive disorder (OCD). OCD is time-consuming and distressing, and can substantially disable functioning at school, at home, and with peers (Piacentini, 2003). Children who do not receive treatment are at risk of psychological difficulties in adulthood, including continued OCD, clinical anxiety and depression, personality disorders, and social maladjustment (Wewetzer et al., 2001). Two-thirds of adult cases of OCD develop in childhood, and adults with OCD have lower employment, poorer academic achievement, and lower marital rates compared to non-OCD adults (Hollander et al., 1996; Koran, 2000; Lensi et al., 1996; Steketee, 1993). The distressing nature of OCD in childhood, accompanying psychosocial impairment and risk of future psychopathology, underscore the need to identify effective treatments. The primary aim of this thesis was to expand knowledge of evidence-based treatments for paediatric OCD. A mixed-methodology approach was employed to examine key issues in this area. The first study used meta-analytic methodology to determine the evidence supporting available treatments for paediatric OCD. An extensive literature search revealed over 100 published reports of treatments, encompassing a broad array of theoretical approaches and treatment strategies. Examples of treatments used for paediatric OCD included psychodynamic therapy, pharmacotherapy, cognitive-behavioural therapy (CBT), hypnosis, family therapy, immunotherapy, and homeopathy.Study 1 comprised the first known meta-analysis of randomised, controlled treatment trials (RCTs) for paediatric OCD. Included studies were limited to RCTs as they are the most scientifically valid means for determining treatment efficacy and provide a more accurate estimate of treatment effect by removing error variance associated with confounding variables. The literature search identified 13 RCTs containing 10 pharmacotherapy to control comparisons (N = 1016) and 5 CBT to control comparisons (N = 161). Random effects modelling yielded statistically significant pooled effect size (ES) estimates for pharmacotherapy (ES = 0.48, 95% CI = 0.36 to 0.61, p < .00001) and CBT (ES = 1.45, 95% CI = 0.68 to 2.22, p =.002). The results support the efficacy of CBT and pharmacotherapy, and confirm these approaches as the only two evidence-based treatments for paediatric OCD. Implications and suggestions for future research are discussed. The effectiveness of CBT provided impetus to further examine this treatment. Group CBT is an understudied treatment modality among children with OCD. It was hypothesised that group CBT would possess efficacy because of the effectiveness of individual CBT for children with OCD, the demonstrated effectiveness of group CBT among adults with OCD, the practical and therapeutic advantages afforded by a group treatment approach, and the embeddedness of the approach in robust psychological theory. The aim of the second study was to evaluate the efficacy of group CBT. The study comprised the largest known conducted randomised, placebo-controlled trial of group CBT for paediatric OCD.Twenty-two children and adolescents with a primary diagnosis of OCD were randomly assigned to a 12-week program of group CBT or a credible psychological placebo. Children were assessed at baseline, end of treatment, and at 1 month follow-up. Outcome measures included the Children’s Yale-Brown Obsessive-Compulsive Scale, global measures of OCD severity, Children’s Depression Inventory, and parent- and child-rated measures of psychosocial functioning. An intention-to-treat analysis revealed that children in the group CBT condition had statistically significantly lower levels of symptomatology at posttreatment and follow-up compared to children in the placebo condition. Analysis of clinical significance showed that 91% of children that received CBT were ‘recovered’ or ‘improved’ at follow-up, whereas 73% of children in the placebo condition were ‘unchanged’. Effect size analysis using Cohen’s d derived an effect of 1.14 and 1.20 at posttreatment and follow-up, respectively. These effects are comparable to results from studies of individual CBT. This study supported group CBT as an effective treatment modality for paediatric OCD and demonstrated that the effect extends beyond placebo and nonspecific treatment factors. In addition to treatment efficacy, the inherent worth of a treatment lies in its adoption by the relevant clinical population. Children with OCD are known to be secretive and embarrassed about symptoms, and there is often a long delay between onset of symptoms and treatment-seeking (Simonds & Elliot, 2001). An important observation during the course of conducting the RCT was that a high rate (39%) of eligible families declined participation.This led to the question, "What barriers prevent participation in group CBT for paediatric OCD?" Qualitative methodology was employed to address this research question. Eligible families that had declined participation in the RCT were contacted and invited to participate in semi-structured interviews that explored reasons for non-participation and positive and negative perceptions of group CBT. The average time between non-participation and interview was 1.33 years (SD = 3 months). Data were collected from nine families and thematic analysis methodology was utilised to identify emergent themes. Failure to participate was predicted by practical and attitudinal barriers. Practical barriers included a lack of time, distance, severity of OCD symptoms, financial, and child physical health. Attitudinal barriers included child embarrassment about OCD symptoms, child belief that therapy would be ineffective, fear of the social aspect of the group, lack of previous success with psychology, lack of trust in strangers, parental concern about the structure of the group, denial of a problem, and â€˜not being ready for itâ€™. Attitudinal barriers more frequently predicted treatment non-participation. Positive and negative perceptions of this treatment modality were informative. Parents showed no differences in preference for individual or group CBT. An important finding was that 56% of the children had not received treatment since parental expression of interest in the group CBT program. Application of the findings to methods that promote service utilisation is discussed.